2012
DOI: 10.1166/jbn.2012.1398
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Preparation of Celastrol-Loaded Polymeric Nanomicelles Using Rotatable Central Composite Design and Response Surface Methodology

Abstract: Celastrol has been found to be a potent anti-inflammatory and antitumor plant derivative recently. Herein we established an accurate reverse phase HPLC (RP-HPLC) determination method of celastrol, and prepared an effective nanoscale drug delivery system from the optimized formulations of celastrol-loaded carboxyl functioned poly(ethylene glycol)-block-poly(propylene glycol)-blockpoly(ethylene glycol)(PEO-block-PPO-block-PEO, Pluronic) polymeric nanomicelles. Rotatable central composite design (RCCD) and respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…To surpass the physicochemical and pharmacokinetic limitations of celastrol and to diminish the effective dose, several methodologies have been tested that can represent useful strategies, such as exosomes (200), lipid nanospheres (201), nanoencapsulation (202), polyamidoamine dendrimer nanocarriers (203), liposomes (204206), polymeric micelles (207, 208), cell-penetrating peptides-coated nanostructured lipid carriers (194, 209–211), sugar-silica nanoparticles (212), and self-microemulsifying drug delivery system (193). For instance, recent data have shown that celastrol-loaded exosomes enhance free celastrol efficacy and reduce dose-related toxicity in lung cancer (200).…”
Section: New Strategies For the Use Of Celastrolmentioning
confidence: 99%
“…To surpass the physicochemical and pharmacokinetic limitations of celastrol and to diminish the effective dose, several methodologies have been tested that can represent useful strategies, such as exosomes (200), lipid nanospheres (201), nanoencapsulation (202), polyamidoamine dendrimer nanocarriers (203), liposomes (204206), polymeric micelles (207, 208), cell-penetrating peptides-coated nanostructured lipid carriers (194, 209–211), sugar-silica nanoparticles (212), and self-microemulsifying drug delivery system (193). For instance, recent data have shown that celastrol-loaded exosomes enhance free celastrol efficacy and reduce dose-related toxicity in lung cancer (200).…”
Section: New Strategies For the Use Of Celastrolmentioning
confidence: 99%
“…The procedure was carried out by taking 0.2 µl of a Celastrol nanoemulgel preparation using uranyl acetate dye 2% (w/v) 0.2 µl, which was dripped on the cooper grid plate. Furthermore, observations were made at a magnifications of 30,000, 50,000 and 100,000 times [25,26].…”
Section: Morphology Of the Preparationmentioning
confidence: 99%
“…The method was developed into peroral, IP, and topical routes. The study results concluded that Celastrol developed into nanotechnology increased the absorption efficiency (EE) to 98.06% with an average particle size of 89.6±7.3 nm ≤100 nm and zeta potential of 87.8±5.8 mV [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the reliable determination methods are essential for the precise pharmacokinetics of the analyte and its novel formulations. Till now, some determination methods of CL in plasma based on HPLC technology and their application in pharmacokinetic studies have been reported [ 18 , 19 , 20 , 21 ]. However, the insufficient selectivity and sensitivity of HPLC methods apparently limit their wide application on in vivo pharmacokinetics such as oral bioavailability studies of CL loaded drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%